Factores de riesgo que inciden en la lumbalgia en pacientes que acuden al Centro de Rehabilitación Física “Freddy Ayala Fisioterapia Funcional” en el cantón Babahoyo periodo junio-septiembre 2024. - Alvarado Burbano, Esthefany Jazmín (2024)
Low back pain is a localized pain in the lower back (lumbar spine), which hinders movement and affects the quality of life, limiting work, recreational and social activities. This musculoskeletal condition is one of the most frequent in patients who come to the physical rehabilitation center "Freddy Ayala Fisioterapia Funcional" in the Babahoyo canton during the period June-September 2024. Our research was carried out with the aim of identifying the risk factors that affect low back pain in patients attending this establishment during the study period, finding that the indicators associated with low back pain are: age, gender, body mass index (BMI), physical activity and occupation. A mixed approach was used to determine the factors that influence this pathology, allowing for a detailed analysis of the potential causes and standardisation of the data using the survey technique; All this was carried out on the basis of inductive-deductive reasoning which, by means of basic, non-experimental, field, correlational and transversal types of research, facilitated the definition of the population and by means of the inclusion and exclusion criteria determined a sample of 25 patients. Through their study, the variables and their relevance in the incidence of this pathology were established, thus promoting preventive ergonomic measures to reduce the prevalence of this condition which afflicts a large part of the population by means of the recommendations put forward.